2016
DOI: 10.3389/fnhum.2016.00120
|View full text |Cite
|
Sign up to set email alerts
|

The Oscillopathic Nature of Language Deficits in Autism: From Genes to Language Evolution

Abstract: Autism spectrum disorders (ASD) are pervasive neurodevelopmental disorders involving a number of deficits to linguistic cognition. The gap between genetics and the pathophysiology of ASD remains open, in particular regarding its distinctive linguistic profile. The goal of this article is to attempt to bridge this gap, focusing on how the autistic brain processes language, particularly through the perspective of brain rhythms. Due to the phenomenon of pleiotropy, which may take some decades to overcome, we beli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 190 publications
(243 reference statements)
2
43
0
6
Order By: Relevance
“…One explanation we contemplated in the present work relates to the possibility of an underlying uniform etiology across the reviewed disorders. This uniformity can be traced back to brain network organization (van den Heuvel and Sporns, 2013 ; Crossley et al, 2014 ; Benítez-Burraco and Murphy, 2016 ). Addressing the parallels that can be observed across different levels of representation (phenome, connectome, dynome, and oscillome) from a phylogenetic perspective, we have established a connection between the hypothesis put forth in the present work and the “syntax-before-phonology” hypothesis of Collier et al ( 2014 ): Syntax is better preserved because it evolved before other domains of language (e.g., morphology and phonology).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One explanation we contemplated in the present work relates to the possibility of an underlying uniform etiology across the reviewed disorders. This uniformity can be traced back to brain network organization (van den Heuvel and Sporns, 2013 ; Crossley et al, 2014 ; Benítez-Burraco and Murphy, 2016 ). Addressing the parallels that can be observed across different levels of representation (phenome, connectome, dynome, and oscillome) from a phylogenetic perspective, we have established a connection between the hypothesis put forth in the present work and the “syntax-before-phonology” hypothesis of Collier et al ( 2014 ): Syntax is better preserved because it evolved before other domains of language (e.g., morphology and phonology).…”
Section: Discussionmentioning
confidence: 99%
“…The important question is why syntactic operations are better preserved in a consistent way across disorders with different genetic etiology. One explanation is that the phenotypic overlaps that we identified are in fact surface reflections of more deeply rooted overlaps at the connectome or even the oscillome (Benítez-Burraco and Murphy, 2016 ). Observing that the hierarchy of brain oscillations has remained remarkably preserved during mammalian evolution (Buzsáki et al, 2013 ), Benítez-Burraco and Murphy ( 2016 ) suggest that language deficits in various cognitive disorders can be traced back to a brain syntax network.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…The second subset consists on strong candidates for language evolution, as compiled by Boeckx and Benítez-Burraco (2014a;2014b) and Benítez-Burraco and Boeckx (2015). These are genes involved in the globularization of the human skull/brain and the cognitive changes accounting for our species-specific ability to learn and use languages (aka our language-readiness), and fulfil the following criteria: they have changed (and/or interact with genes that have changed) after our split from Neanderthals/Denisovans (including changes in their coding regions and/or their epigenetic profile); they play some known role in brain development, regionalization, wiring, and/or function; and/or they are candidates for language dysfunction in broad cognitive disorders, particularly, ASD and schizophrenia (SZ) (see Benítez-Burraco and Murphy, 2016;Murphy and Benítez-Burraco, 2016; 2017 for details about their role in language processing).…”
Section: Methodsmentioning
confidence: 99%
“…MED13L is implicated in neural crest induction and is highly expressed in the cerebellum after birth [175] . MED13L relates functionally to EP300 and CREBBP products, link proteins between the FOXP2 and ROBO1 pathway [176] . In a case-report described by Jimenez-Romero et al [177] a SNP was identified in MED13L (chr12: 116675396A> G, G, GRCh37), which associates with a profound language disturbance in the expressive domain, cognitive retardation, behavioral disturbances and an autism-like phenotype.…”
Section: Autism-spectrum Disordersmentioning
confidence: 99%